Suitability of microwave application to heat reclaimed asphalt and crushed aggregates as an energy efficient method in the production of half warm mix - Nieftagodien, Riyaaz (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.